A Descriptive Study on Determinant Factors of Females Who Accepted Sterilization in Rural Vadodara - Pandit, Niraj B; Patel, Tushar A (National Journal of Community Medicine, 2013)
Background: National Population Policy 2000 focuses on population stabilization for which wider use of permanent method of contraception is essential. The present study was conducted with objectives of understanding the determinant factors for female sterilization and assessing the knowledge of permanent method of contraception of the females undergoing female sterilization. Methods: Interview based descriptive study among females visiting hospital for sterilization was conducted in rural Vadodara. The questionnaire included subject’s socio-economical data and determinant factors, knowledge and practice about various aspects of female sterilization and their usage of temporary methods of contraception in past. All women visiting during study period of three months were included in the study. Results: Among 81.92% of women gender of the last child was male. 59.0% women were having one male child and 39.8% women were having more than one male child. 45.8% women had three or more live children. Only 37.35% of women accepted sterilization within first year of last delivery. Past history of use of temporary method of contraception was present in 48.20% women of which 37.35% were using condoms. Knowledge about failure rate of tubal ligation, its complications and about non scalpel vasectomy was present in 8.5%, 18.1% and 48.20% respectively. Conclusions and Recommendations: Among women who accepted sterilization 45.8% of women were having three or more children. For population stabilization it is essential that females with two or less children accept sterilization. Attempts should be made to change preferences for at least singular male child.